Perbandingan Pemikiran Nasionalisme Adolf Hitler, Sukarno dan Gamal Abdul Nasir - Fransiskus X. Gian Tue Mali; Martinus Yulianus Mite (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
Nationalism has historically been embraced by various nations and countries with different characteristics and characteristics. The focus and purpose of this article is to compare the thinking of nationalism in the perspective of Adolf Hitler and Sukarno. In this study using a qualitative approach. The data is obtained from literature study. The results showed that the nationalist thoughts of Adolf Hitler, Sukarno and Gamal Abdul Nasir were constructed based on indicators social, economic, political and cultural conditions in the midst of their respective nations and countries. Hitler's ideas of nationalism were based on the superiority of the Aryan race and Lebensraum (expansion), which carries out the politics of imperialism. Sukarno formulated the idea of nationalism based on the values of diversity, liberation, humanity, brotherhood between nations and countries as well as anti-colonialism and anti-imperialism. Meanwhile, the concept of Arab nationalism echoed by Nasir is based on the similarity of language, historical background, culture and religion (Islam). Among the three have differences and similarities in formulating the concept of nationalism. The three concepts of nationalism have a universal equation, namely unity, which is the main key in restoring the dignity of each nation amidst a situation of crisis and foreign domination.